2017
DOI: 10.1038/cddis.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

NCAPH plays important roles in human colon cancer

Abstract: Colon cancer (CC) is one of the major malignancies worldwide, whose pathogenesis is complex and requires the accumulated alteration of multiple genes and signaling pathways. Condensins are multi-protein complexes that play pivotal roles in chromosome assembly and segregation during mitosis, meiosis and even tumorigenesis. Using tissue microarrays by immunohistochemistry and hematoxylin–eosin staining, we found that non-SMC condensin I complex subunit H (NCAPH) in colon cancerous tissues was higher than that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 39 publications
14
80
0
Order By: Relevance
“…A recent report showed that NCAPH is upregulated in colon cancer tissue, and its high expression correlates with poor prognosis. Furthermore, inhibiting NCAPH promotes cell apoptosis and cell cycle arrest at the G2/M phase, and exerts antitumor effects in colorectal cancer in vitro and in vivo . Importantly, our present data showed that regardless of the expression of AR, the silencing of NCAPH inhibited the aggressiveness of PCa cells.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A recent report showed that NCAPH is upregulated in colon cancer tissue, and its high expression correlates with poor prognosis. Furthermore, inhibiting NCAPH promotes cell apoptosis and cell cycle arrest at the G2/M phase, and exerts antitumor effects in colorectal cancer in vitro and in vivo . Importantly, our present data showed that regardless of the expression of AR, the silencing of NCAPH inhibited the aggressiveness of PCa cells.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, inhibiting NCAPH promotes cell apoptosis and cell cycle arrest at the G2/M phase, and exerts antitumor effects in colorectal cancer in vitro and in vivo. 33 Importantly, our present data showed that regardless of the expression of AR, the silencing of NCAPH inhibited the aggressiveness of PCa cells. This is the first study to report that dysregulated NCAPH is deeply involved in CRPC pathogenesis, and its expression was directly controlled by antitumor miR-199a/b-3p.…”
Section: Chka Cdc6 Ncaphsupporting
confidence: 47%
“…C21orf45, also known as MIS18A, is a kinetocore protein belonging to the Mis18 complex assembly that is crucial for CENPA deposition at the centromere [26,27]. DEPDC1 is highly expressed in M phase and its silencing caused mitotic defects [28][29][30][31] and NCAPH is a regulatory subunit of the condensin complex required for the conversion of interphase chromatin into condensed chromosomes [32][33][34]. Overall, their altered expression could participate in the definition of the aberrant mitotic regulation.…”
Section: P53 Mut Downstream Targets Are Differently Modulated In Pt-rmentioning
confidence: 99%
“…NCAPH encodes a regulatory subunit in the non‐SMC condensing I complex and is required for the conversion of interphase chromatin into condensed chromosomes . Previous studies have revealed that abnormal expression of NCAPH is associated with colon cancer and prostate cancer . However, there have been no relevant reports about the clinical relevance and functional role of NCAPH in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies have revealed that abnormal expression of NCAPH is associated with colon cancer and prostate cancer. 10,11 However, there have been no relevant reports about the clinical relevance and functional role of NCAPH in HCC. In this study, we aimed to explore NCAPH expression in HCC tissues and investigate the functions of NCAPH in HCC cells.…”
Section: Introductionmentioning
confidence: 99%